2015
DOI: 10.1186/s12884-015-0507-2
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight by gestational age and congenital malformations in Northern Ethiopia

Abstract: BackgroundStudies on birth weight and congenital anomalies in sub-Saharan regions are scarce.MethodsData on child variables (gestational age, birth weight, sex, and congenital malformations) and maternal variables (gravidity, parity, antenatal care, previous abortions, maternal illness, age, medication, and malformation history) were collected for all neonates delivered at Ayder referral and Mekelle hospitals (Northern Ehthiopia) in a prospective study between 01-12-2011 and 01-05-2012.ResultsThe total number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 34 publications
(37 reference statements)
3
46
2
2
Order By: Relevance
“…In humans, congenital malformations seem to be the most important factor that determines low birth weight [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In humans, congenital malformations seem to be the most important factor that determines low birth weight [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Lack of dietary diversity and micronutrient-dense food consumption and poor child feeding practices contribute to the high rate of child under nutrition. Various reports also indicate that underweight in children is mainly caused by inadequate food intake [ 7 , 8 ], repeated infections [ 9 – 11 ], low parental education [ 12 14 ], lack of sanitation [ 15 ], poor feeding practices [ 16 ], no ANC [ 17 19 ], residence [ 20 ], child rearing practices [ 21 ], economic [ 21 , 22 ], social, and cultural factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence in LMICs (16.5%) is twice higher than in high-income countries (7%) [2]. In Ethiopia, LBW rate varies across geographical areas, which ranges from 8% to 54% [3][4][5][6], showing a huge variation across geographical settings and time periods. A recent systematic review showed a pooled estimate of 17.3% in Ethiopia [7], which implies it still remains an important public health problem in the country.…”
Section: Introductionmentioning
confidence: 99%